Chemistry of Brazilian green coffee and the quality of the beverage, 5: Multiple linear regression analysis - Amorim, H.V.; Cruz, V.F.; Teixeira, A.A.; Malavolta, E. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Multiple linear regression analysis was performed to try to relate the quality of the coffee beverage to its chemical composition. Six samples of each beverage quality (Soft, Hard, Riada and Rio) were classified by professional tasters from the I B.C., and 24 cup tests were performed for each sample. The chemical analyses of total free carbohydrates, reducing sugars, total nitrogen, proteins soluble in NaCl, NaOH and phosphate buffer, total chlorogenic acid, phenols soluble in methanol and water, hydrolyzable phenols and electrophotogenic behavior of the proteins were considered in the regression analysis.